Evaluation of antioxidant, analgesic, anti-inflammatory and antispasmodic activity and genotoxic effect of micromeria fruticosa subsp brachycalyx in vitro and in vivo - KABASAKAL, LEVENT; TAŞKIN, TURGUT; AYDEMİR, SEZGİN; BECEREN, AYFER (My University, 2021)
EVALUATION OF ANTIOXIDANT, ANALGESIC AND ANTIINFLAMMAUTORY ACTIVITY AND GENOTOXIC EFFECT OF MICROMERIA FRUTICOSA SUBSP BRACHYCALYX IN VITRO AND IN VIVO1Celikkol I., 2Beceren A., 3Kabasakal L., 4Taskin T., 5Aydemir S.1Marmara University, Institute of Health Sciences, Department of Pharmaceutical Toxicology Istanbul, Turkey, celikkolisik@gmail.com 2Marmara University, Department of Pharmaceutical Toxicology, Istanbul, Turkey, ayfertozan@hotmail.com 3Marmara University, Department of Pharmacology, Istanbul, Turkey, lkabasakal@gmail.com 4Marmara University, Department of Pharmacognosy, Istanbul, Turkey, turguttaskin@marmara.edu.tr 5Marmara University, Vocational School of Health Services, Department of Medical Services and Techniques, Istanbul, Turkey, szgnaydemir@gmail.comIntroduction: Today, antioxidants have been using diversely in various medical conditions. Therefore, there are growing interest for discovering and developing more effective and safer antioxidants derived from natural sources. Certain Micromeria species were identified as a rich source of antioxidant agents (1). This study aimed to investigate possible antioxidant activity and genotoxicity of Micromeria fruticosa subsp brachycalyx in methanol extract both in vitro and in vivo.Materials and Methods: In vitro antioxidant activity of Micromeria fruticosa subsp brachycalyx in methanol extract was evaluated by DPPH, ABTS, FRAP and CUPRAC assays. In vivo analyses performed on Balb/c mice that divided to three groups (n=6 for each group) as control group (%0,04 Carboxymethyl cellulose solution (CMC), 0,1 mL/10 g, p.o.), positive control group (Indomethacin in %0,04 CMC, 10 mg/kg, p.o.) and treatment group (Micromeria extract in %0,04 CMC, 200 mg/kg, p.o.) and each regimen was applied for 10 days. Myeloperoxidase levels were analyzed in mice liver and kidney tissues. Genotoxic effect was determined in mice blood with Comet Technique. The 8-hydroxy-2’-deoxyguanosine was analyzed in mice liver and kidney tissues with commercial ELISA kit. Results: The results showed that plant extract showed stronger DPPH radical scavenging activity, however, lower ABTS, CUPRAC and FRAP values versus to standards. According to the graph, which shows the elapsed time (second) in pain behavior versus time (minute) for each group, treatment group exhibited its efficacy in late phase (20-30 min) similar with indomethacin group. Myeloperoxidase levels in liver tissues of the extract group were significantly lower compared to the control group (p<0.05). Myeloperoxidase levels in kidney tissues of the extract group were not significantly different compared to both control and indomethacin group. Micromeria fruticosa subsp brachycalyx extract exerted no genotoxic effect on DNA similarly both control and indomethacin group.Conclusions: Our study showed that Micromeria fruticosa subsp brachycalyx has a potential antioxidant activity. It has also been contributed to raise awareness to this species in terms of its safety with the obtained results. Therefore, the usage of this species as natural antioxidant source is promising for new drug candidates.Acknowledgements:Not available.References: 1. Salameh N et al., (2020) Screening of Antioxidant and Antimicrobial Activity of Micromeria fruticosa serpyllifolia Volatile Oils: A Comparative Study of Plants Collected from Different Regions of West. BioMed Research International, 1-7.
Keywords: Eczacılık; Sağlık Bilimleri; Pharmacology and Therapeutics; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Yaşam Bilimleri; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Life Sciences